Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Plugging the equation $y''+y'=0$ into Wolfram Alpha yields the following solution:

$$y(x) = c_2-c_1 e^{-x}.$$

This has me stumped because my textbook states that in the case of $b^2-4ac > 0$.

"If root 1 $r_1$ and root 2 $r_2$ are two real and unequal roots to the auxiliary equation $ar^2 + br + c =0$, then

$$y = c_1e^{r_1x} + c_2e^{r_2x}$$

is the general solution."

Based of my book, the solution to the above problem would be

$$y=c_2+c_1 e^{-x}$$

so which one's right?

share|cite|improve this question
Both are right. Arbitrary constant means arbitrary constant. – André Nicolas Jul 11 '11 at 13:42
Be careful with signs-- the equation you typed into Wolfram Alpha is y''+y'=0, and your question is about y''-y'=0. – Jonas Kibelbek Jul 11 '11 at 13:44
thanks, I fixed that. – Fred W. Jul 11 '11 at 13:49

Both are correct.The only difference is the sign of the constant $c_1$, which does not matter once you plug in your initial conditions.

You can of course verify that both are correct solutions. Let's call the solutions $y_1$ and $y_2$: $$\begin{align} y_1 = c_2 - c_1 e^{-x} \\ y_2 = d_2 + d_1 e^{-x} \end{align}$$

Now you get: $$y_1'' + y_1' = -c_1e^{-x} + c_1e^{-x} = 0$$ and $$y_2'' + y_2' = d_1e^{-x} - d_1e^{-x} = 0$$

share|cite|improve this answer
oh, that makes an incredible amount of sense. Thanks a bunch! – Fred W. Jul 11 '11 at 14:00
You are welcome. – Calle Jul 11 '11 at 16:49

HINT $\rm\quad \langle 1,\:e^{-x}\rangle\ \cong\: \langle 1, -e^{-x}\rangle\ $ as vector spaces.

share|cite|improve this answer
Were comments deleted from this conversation? – The Chaz 2.0 Jul 13 '11 at 17:12
@The Chaz Yes, thanks for the heads-up. I just deleted my comments too since they are meaningless without the comments they replied to. – Bill Dubuque Jul 13 '11 at 17:33
@BillDubuque Welcome back! – Pedro Tamaroff Feb 23 '12 at 20:57

$ y''+y'=0 \\ y'=t(x) \ \to y''=t'(x) \\ t'+t=0 \\ \frac{dt}{t}+dx=0 \\ \ln |t|+x=C \\ \ln|t| + \ln e^x = \ln e^{C} \\ t \cdot e^x=C_1 \\ y' \cdot e^x =C_1 \\ dy=C_1\frac{dx}{e^x} \\ \int dy=C_1 \int \frac{dx}{e^x} \\ ...$

share|cite|improve this answer

so see from your definition that if $b^2-4ac$ is more than zero, let's check it,

$y^{''}-y'=0$ is in form $k^2-k=0$ yes? so $k(k-1)=0$ from here there is two chance $k=0$ or $k=1$ or use $r_1$ and $r_2$ as you like so $r_1=0$ and $r_2=1$ and put them in general solution

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.